Development of Participative and Collaborative Learning Evaluation Tool of Academic Writing to Enhance Students' Social and Emotional Intelligence - Supriyadi Supriyadi; Muslimin Muslimin (AIBPM Publisher, 2020)
The study aimed to develop a participative and collaborative learning evaluation tool for academic writing to enhance students' social and emotional intelligence. The developmental research laid its emphasis on the importance of facilitating a valid and reliable learning evaluation tool to measure the extent of success of academic writing learning. The study integrated R2D2 and RDR models as the development model of the evaluation tool. The R2D2 model comprised three focuses: determination process, design and development, and dissemination. In the meantime, the RDR model also involved three focuses: initial observation, tool development, and implementation of effectiveness test activity. Therefore, the development process of the evaluation tool consisted of four steps (based on the integration of R2D2 and RDR models): 1) initial observation, 2) determination process, 3) tool design, and 4) tool development. Moreover, qualitative and quantitative data were employed in the study; all data were acquired from the learning process, as well as the students, lecturers, practitioners, and relevant experts. The data were further analyzed by employing domain analysis and paired sample t-test statistical analysis. The development process results in a product in the form of four learning evaluation tools to measure the learning outcomes of academic writing subject. The tools involved: assessment rubric, portfolio, observation sheet, and learning journal. According to the effectiveness test result, the evaluation tools are deemed as valid and reliable to be implemented in evaluating the learning process and learning outcomes of academic writing subject.